Benign Fibroepithelial Polyp of Renal Pelvis in a Patient with Familial Adenomatous Polyposis: A Successful Percutaneous Nephroscopic Management Strategy - Nikhil Vasdev; Philippa Holmes; Katie Senior; Philip Haslam; Tahseen Hasan; Trevor Dorkin (Advances in Urology)
We present a rare case of a benign fibroepithelial polyp of the renal pelvis in a patient with familial adenomatous polyposis. In our paper we describe a new minimally invasive technique developed in our unit using an amplatz goose neck snare via a percutaneous nephroscope sheath in the management of the benign fibroepithelial polyp of the renal pelvis and present a current review of management strategies in literature.